TEKNOLOGI BERBASIS ANIMASI SEBAGAI SARANA EDUKASI ANAK DALAM MENCEGAH PENULARAN HEPATITIS AKUT DI SEKOLAH - Ana Nistiandani; Lantin Sulistyorini; Siswayo; Jon Haffan Sutawardana; Mulia Hakam; Mochammad Ubaidillah (LP2M Universitas Hasanuddin, 2024)
TEKNISI is a technology that has modified its appearance in animated videos. TEKNISI is designed to increase children's knowledge to prevent transmission of acute hepatitis in the school environment. TEKNISI contains clean and healthy living behavior (PHBS) material. Children under 16 years of age are the main concern of Acute Hepatitis of Unknown Aetiology (acute hepatitis). The purpose of this activity is to increase participants' knowledge of clean and healthy living behavior (PHBS) in preventing hepatitis transmission in schools. The method is carried out through technology-based health education called